Access Policy in Capital Account Crises. (Policy Papers; Policy Paper ;, 2002)
The Fund's decisions to lend to member countries in amounts well above the access limits for Mexico (1995), and since then, have raised important questions about the role of the Fund in crisis resolution and the appropriate size of Fund access in capital account crises. This paper reviews past experience in exceptional access cases and considers strengthened conditions, procedures and safeguards for guiding decisions on Fund programs in these exceptional circumstances where Fund financing above normal access limits may be appropriate.